Macro-Fiscal Implications of Health Care Reform in Advanced and Emerging Economies. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
This paper provides an analysis of the developments in public health spending over the past 40 years, as well as projections of public health spending for 50 advanced and emerging countries over 2011-50. The paper also quantifies the effects of specific health reforms on the growth of public health spending in advanced economies by drawing on a range of analytical approaches, including country case studies. The challenges facing emerging economies as they seek to expand coverage of health care in a fiscally sustainable manner are also examined.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet